The Arabic-Islamic Philosophy, Its Definition and Historical Significance - Alić, Salih H. (Prilozi za orijentalnu filologiju, 2017)
The subject under the diseussion in this paper is not approached from any particular philosophical school or theory, but, rather, as a historical problem with regard to the origins, meaning and the role of that philosophy, above ali, in the Middle Ages. It is called Islamic because it was developped and cultivated in the area under the impact of Islam, or within the clearly defined Islamic civilization, in spite of a permanent conflict betvveen faith and rea- son, auctoritas and ratio, as was the case also with Judaism and Christianity. It may also be called Arabic, but meraly because its main works are written in the Arabic language. Of particular importance for the inception of that philosophy is the fact that Islam, both as religion and a culture, arose as a result of special hellenistic or hellenizing forces, notvvithstanding its being based initially on the revelation. It was a meeting ground of several streams from different sources and languages but ultimatily expressed, in one language, Arabic, and formed in agreement with ideas and aspirations inspired by Islam as religion and vision of the worlđ. Thus the sources of Islamic philosophy may be said to be tvvofold: from within the Islamic tradition, strictly speaking, with its intrinsic problems, touching individual faith and public responsibility, human action and divine omnipotence, qualities and quantities of faith, the question of perfection both of the individual and the society, as posed by the Qur’an as a revealed word and inevitably dictated by the ali pervading reality. This genu ine Islamic philosophy found its facit in the scholastic or dialecti- cal theology, kalam, cultivated by various schools, such as mu’tazila, ğabriyya, murği’a, ash’ariyya, and many other sehools, with a wide range of conflicting wiews. But even these, Islamic schools were influenced by ideas from various sources, manly from Greek philosophy. The second source was the Greek heritage readly taken aver and cultivated by the Muslims, resulting in nume- rous translations and commentaries of Greek philosophical Works, mainly of Plato and Aristotle but also of others of neoplationic school. This was falsafa, philosophy, and those who cultivated that branch of knowledge were called falasifa, philosophers, in contradistinction to kalam and mutakallimun. Both of these philosophies, as represented by al-Kindi, al-Farabi, Ibn Sina, Aver- roes, al-Ghazali, to name only a few, had a large share in transmitting the Greek heritage to the Christian West and in influencing the sholastic philosophy, and even the theology, of Thomas Aquinas, Duns Scotus, Roger Bacon and the entire philosophy of the Middle Ages.